The Influence of Marketing Mix on Customer Satisfaction in Cinematography Extraculicular Training Program Company Cinema Innovator Bandung Branch - Hani Azizah; R. Iim Takwim; Reni Herniawati (Program Studi Administrasi Bisnis, 2022)
This study aims to determine the effect of the marketing mix consisting of product, price, place and promotion on customer satisfaction in the Cinematography Extracurricular Training program for the Bandung Branch of Cinema Innovator Company. The research method used is a survey research method. Data collection techniques by observation, interviews, literature studies and distributing questionnaires to 21 respondents. The sampling technique used is purposive sampling. The data analysis used was multiple regression analysis with the help of SPPS 26. The results showed that the marketing mix of product, price and place had no and no significant effect on customer satisfaction, meanwhile, promotion had a significant effect on customer satisfaction. Simultaneously product, price, place and promotion have a significant effect on customer satisfaction. The marketing mix variable consisting of product, price, place and promotion has an effect of 62.3% on the customer satisfaction variable, while 37.7% is influenced by other variables not examined.